ANALISIS STAKEHOLDERS DALAM KEBIJAKAN PROGRAM DANA BERGULIR (PDB) SAMISAKE DI KOTA BENGKULU - Sri Indarti (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2019)
Abstract: Samisake's GDP policy has been running in the 6th year, where the policy began to be implemented in 2013, which already has a regulation in the form of Perda No. 12 of 2013 concerning Samisake Revolving Funds, Perwal Number 27 of 2013 concerning technical guidelines for revolving funds and Perwali no. 17 of 2018 concerning the Establishment of the Samadake Revolving Fund Management Unit in the Bengkulu City Small and Medium Enterprises Cooperative Office. This policy is targeted to be an embryo of a revolving fund policy in favor of the public interest. Policy information shows that there are problems and challenges in realizing policy targets in the form of expanding employment opportunities or creating new jobs, reducing unemployment and strengthening regional competitiveness. This study is intended to conduct stakeholder analysis on the effectiveness of Samisake's GDP policy. This study was a qualitative study, with informants from the Head and staff of UPTD Samisake, staff of cooperatives and SMEs, administrators and members of the cooperative distributing Samisake GDP funds, communities receiving samisake funds and program companions. Research results show that stakeholders in this policy are. Samisake UPTD, Regional Head, Office of Cooperatives and SMEs, Microfinance Institutions, Villages, Assistance, DPRD, BAPPEDA and Non-Governmental Organizations. The results of this study indicate that policies have not been effective in accordance with the targets of policy regulation, both in terms of management and policy impacts. Financial Circulation is found in MFIs, banks, and the community receiving the program, with limited financial transparency and responsibility. The findings of this study are, it needs mechanisms, systems, and assistance that are focused in order to achieve policy targets. Policy advocacy is needed to improve policy performance in the future